2016
DOI: 10.1021/acs.cgd.6b00783
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Morphology and Growth in Annealed Rubrene Thin Films

Abstract: While controlled crystallization of organic thin films holds great potential for enhancing the performance of electronic devices, quantitative understanding of the processes involved is limited. Here, we characterize the thin film crystal growth of the organic semiconductor rubrene during annealing using polarized optical microscopy with a heated stage for in situ measurements, followed by atomic force microscopy and X-ray diffraction. During annealing, the film undergoes transitions from predominant growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 57 publications
1
38
1
Order By: Relevance
“…Two very recent papers have presented results which are closely connected to the work presented here. Fielitz and Holmes showed that glasses of rubrene prepared by vapor deposition can crystallize into different polymorphs depending on subsequent temperature treatment 40 . Each of our three glasses also shows this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Two very recent papers have presented results which are closely connected to the work presented here. Fielitz and Holmes showed that glasses of rubrene prepared by vapor deposition can crystallize into different polymorphs depending on subsequent temperature treatment 40 . Each of our three glasses also shows this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible origins for the aggregation. The first is an insufficient diffusion of adsorbed molecules to evenly spread the molecules at T substrate before they become aggregated, and the second is residual heat on substrates inducing nucleation, thus growing into aggregated particles [ 24 , 36 , 39 , 40 , 41 , 42 ]. To evaluate the latter possibility and diminish it, a fast cooling step that drops T substrate down to room temperature in 300 s ( Figure 1 b) is employed by blowing air through the substrate region using an electric fan after the designated time of deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The successful formation of ultrasmooth rubrene film owes mainly to the adequate control of substrate temperature, allowing adsorbed molecules to diffuse on a substrate but prohibiting aggregation or nucleation [ 24 , 36 , 39 , 40 , 41 , 42 ]. When T substrate is higher than 85 °C for more than 100 s during the slow cooling of the substrate ( Figure 1 b), very rough surfaces containing aggregates are formed, thus implying that nucleation starts at this condition ( Figure 2 a–c).…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated the effect of epitaxial molecular doping on thin-film rubrene crystal's structural and charge transport properties which has not been proven to be possible with the conventional tube-furnace method. Amorphous rubrene thin films deposited on oxide surfaces might be transformed into highly crystalline rubrene thin films by thermal annealing [152,153]. Using a thin amorphous underlayer, this approach can be generalized to grow crystalline rubrene thin films on a variety of surfaces, from oxides to metals (Figure 21).…”
Section: New Materials For Vertical Organic Thin-film Transistorsmentioning
confidence: 99%